Reliability of shoulder abduction muscle endurance measured using isokinetic dynamometry - Micheletti, J. K.; Andersen, L. L.; Machado, A. F.; Lopes, J. S. S.; Souto, L. R.; Pastre, C. M. (Science & Sports, 2021)
Objective To evaluate reliability of performance and metabolic expenditure during a shoulder abduction endurance test with isokinetic dynamometer.